ORGANIZATIONAL FOUNDINGS, DISBANDINGS, AND THE COVID-19 PANDEMIC: EVIDENCE FROM THE TURKISH CONSTRUCTION SECTOR (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The present study aims to understand the effect of the macro-level economic phenomena observed within a specific time interval on the founding (birth) and disbanding (deaths) of organizations in the construction sector of Turkey that has been growing steadily for many years. In addition, the effects of the COVID-19 pandemic were also taken into consideration.Methodology: The construction sector in Turkey was analyzed within the framework of the theoretical infrastructure of organizational ecology, i.e. a theoretical perspective that has not received enough attention, except in North America, as an organizational community, while joint-stock, limited, and cooperative companies were also analyzed as organizational populations. Focusing on the period between January 2017 and December 2020, a number of foundings and disbandings of joint-stock, limited and cooperative companies operating in the construction sector, the house price index and house sales statistics, which are thought to affect these rates, were used as data. Additionally, the COVID-19 pandemic period between March 2020 and December 2020 was included in the analysis as a dummy variable. The ARDL bounds test was used for data analysis.Results: The findings indicate differentiated effects of the house price index, house sales statistics, and the COVID-19 period on both the organizational community of the construction sector and the aforementioned populations.Conclusion: The results, which are expected to contribute to business economics and organizational theories, studies on the construction sector, knowledge of the evaluation of socioeconomic effects of the COVID-19 pandemic and future studies, were obtained in the study.